PENGARUH STRES KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP INTENSI TURNOVER (Studi padaLembagaPengelola Dana Bergulir Koperasi danUsaha Mikro, Kecil dan Menengah ) - Nurmalitasari Indah Wisantyo; Harries Madiistriyatno (Universitas Mercu Buana, 2015)
Abstract: The purpose of this research is to examine and analyze the effect of work stress, work discipline, and job satisfaction on turnover intention. Sampling method using proportionate stratified random sampling. The data is taken directly using a questionnaire with 72 respondents employees at Lembaga Pengelola Dana Bergulir, Koperasi dan Usaha Mikro, Kecil, dan Menengah (LPDB-KUMKM). The methodof analysis usedin this research is multiple linear regression. Research shows job stress, work discipline, and job satisfactionto gether significantly influence turn over intention. This means that variation turn over intention (Y) can be explainedby the three independent variables work stress (X1), work discipline (X2), andjob satisfaction (X3). The results of the t test, showed that job satisfaction is a negativeand significant effect on turn over intention with while work stress and work disciplinehas possitive effect on turn over intention, but not significant. Job satisfaction variables are variables that most influence on turn over intention.Keywords: job stress, work discipline, job satisfaction, turnover intention.